(untitled) (Labor and Human Development Law Journal, 2018)
This study intends to analyze, from a qualitative point of view, three decisions of the Superior Labor Court (TST) regarding work in conditions analogous to slavery. The purpose is to verify the compatibility of these decisions with the understanding of the Federal Supreme Court (STF) and the Superior Court of Justice (STJ) on the subject. Secondarily, the law, doctrine and, especially, STF and STJ decisions on the subject will be used as research sources in criminal law, linking the understanding in criminal matters with the understanding of the subject at hand. In summary, the present study has as its scope to comparatively identify the understanding of the decisions of the Superiors Courts regarding issues involving work in conditions analogous to that of slave. KEYWORDS: Slavery. Superior Labor Court. Description. Employers’ Registry. Dirty list.